2021
DOI: 10.18844/wjet.v13i3.5951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pre-service teachers' views on their ability to use instructional technologies

Abstract: In recent times, educational technologies have gained grounds in many fields of study. The use of technology to facilitate learning has increased over the past decade, but related problems in education and training are still on the surge. The aim of this study is to determine the opinions of prospective teachers about the skill levels of using and preparing the internet, computer and instructional technology according to different variables. The study was applied to the senior students studying at the classroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The findings by Ciptaningrum et al (2021) are consistent with those of Bilici et al (2016) and Koehler et al (2014) that teachers need to possess technology, TPACK to effectively integrate technology in their classrooms. Some literature shows that though pre-service teacher trainees acquire some technology skills in teacher education, many of them face challenges in planning technology-driven lessons and teaching with technology during school practice (Kisalama & Kafyulilo, 2012;Mandera, 2018;Ramazanova et al, 2021;Jita, 2018;Wetzel et al, 2014). Alsharief (2018) revealed that more than 50% of the preservice teacher trainees at the teachers college in Gulf State did not have the required skills to confidently integrate technology into their lessons.…”
Section: Pre-service Teacher Trainees' Competencies To Integrate Inst...mentioning
confidence: 99%
“…The findings by Ciptaningrum et al (2021) are consistent with those of Bilici et al (2016) and Koehler et al (2014) that teachers need to possess technology, TPACK to effectively integrate technology in their classrooms. Some literature shows that though pre-service teacher trainees acquire some technology skills in teacher education, many of them face challenges in planning technology-driven lessons and teaching with technology during school practice (Kisalama & Kafyulilo, 2012;Mandera, 2018;Ramazanova et al, 2021;Jita, 2018;Wetzel et al, 2014). Alsharief (2018) revealed that more than 50% of the preservice teacher trainees at the teachers college in Gulf State did not have the required skills to confidently integrate technology into their lessons.…”
Section: Pre-service Teacher Trainees' Competencies To Integrate Inst...mentioning
confidence: 99%